The importance of the organization of independent work of students of a medical university in the form of distance learning - Kutsak, A. V.; Куцак, Алла Валеріївна (My University, 2020)
Introduction. Health care reform in Ukraine requires the training of highly qualified medical personnel. Today, higher medical education is based on a competency-based approach, which provides for the improvement and optimization of the educational process and is ensured by the use of modern methods and technologies. Higher education is gradually moving from the transfer of information to the guidance of students mastering the skills of independent work, which is a special form of educational activity and is aimed at developing students' independence, their assimilation of a set of knowledge, skills, and abilities [1]. The purpose of independent work is the acquisition of additional knowledge by students in academic disciplines, verification of the acquired knowledge in practice, the development of certain research and professional skills and abilities. Independent work, in which the student learns the necessary knowledge, masters the skills and abilities, learns to work systematically, to think, forms his own style of mental activity, is extremely important in the educational process. Thanks to the controlled independent work of students and the possibilities of modern information and communication technologies, universities have the potential to prepare a future specialist. A modern competent specialist must be educated, mobile, capable of continuous self-education, self-improvement and raising the level of knowledge [2].